Primeval Wilderness as Consolation in Hans Heysen’s Painting - Zhang, Chunyan (Advances in Social Sciences Research Journal, 2023)
During the period of the 1920s and 1930s, representations of “authentic”, “wild” and “primeval” nature with a positive force and a sense of genuine beauty appeared in Australian painting, especially in the outback paintings of Hans Heysen (1877-1968). In his works, an admiration of the outback and the bush replaced the radical representations of the human battle against nature. This kind of representation demonstrates the attitude of certain Australian artists towards “wild” Australian nature (especially the outback and the bush) changed from perception of it as “alien” and “threatening”, to a growing sense of identification with it.